Gain-saturated repetitive soft X-ray lasers with wavelengths spanning 9-30 nm and lasing down to 7.4 nm - Alessi, David Alan, author; Rocca, Jorge J., advisor; Lee, Siu Au, committee member; Menoni, Carmen S., committee member; Marconi, Mario C., committee member (Colorado State University. Libraries, 2011)
This dissertation describes the development of table-top soft X-ray lasers with wavelengths ranging from 30 nm to 7.4 nm. The laser transisitons occur within collisionally excited states of nickel-like and neon-like ions which are created from laser ablation of solid targets. A Nd:glass slab laser system was developed to provide 20J (and then upgraded to 40J) of laser light at 527 nm for pumping a table-top chirped pulse amplification Ti:sapphire laser. With this increase in pump energy, the Ti:sapphire system is capable of producing 12J uncompressed laser pulses at a 1Hz repetition rate. Stretched and compressed pulses from this Ti:sapphire laser system operating near 800 nm are used to both ionize the material to a high degree and heat the free electrons in these plasmas to temperatures required for high gain. Simulations from a 1.5D hydrodynamic/atomic model indicate a peak gain of 90 cm-1 for the 8.8 nm laser transition in nickel-like lanthanum is reached with an electron temperature of ~850 eV and a density of 6×1020 cm-3. By using the grazing incidence pumping geometry, gain saturated operation was demonstrated in the 2p53p 1S0 →2p5 3s 1P1 transition of neon-like titanium (λ = 32.6 nm) and vanadium (λ = 30.4 nm), as well as in the 3d94d1S0→3d9 4p1P1 transition in nickel-like tellurium (λ = 10.9 nm) and lanthanum (λ = 8.8 nm). Strong lasing was also demonstrated in the same neon-like transition in chromium (λ = 28.6 nm), as well as the same nickel-like transition in cerium (λ = 8.5 nm), praseodymium (λ = 8.2 nm), neodymium (λ = 7.9 nm) and samarium (λ = 7.4 nm). This is the first demonstration of the generation of bright gain-saturated sub-9-nm wavelengths with a table-top laser operating at 1-Hz repetition rate. The short wavelength, microjoule pulse energy, picosecond pulse duration and repetitive operation of these lasers will enable new applications such as sequential imaging of ultrafast nano-scale dynamic phenomena to be realized on a table top.
Keywords: EUV lasers; soft X-ray lasers; solid state lasers; sub 10 nm lasers; ti:sapphire; x-ray lasers